Peluang dan Tantangan Undang-undang Desa dalam Upaya Demokratisasi Tata Kelola Sumber Daya Alam Desa: Perspektif Agraria Kritis - Shohibuddin, Mohamad (Masyarakat: Jurnal Sosiologi, 2016)
Law Number 6 of 2014 on Village—apart from its political contribution in democratizing statevillage relation—has a fundamental limitation on natural resource issues in the village in the light of agrarian and ecological crises. This Law offers a minor elaboration on natural resource issues and provides limited authority to the village on this field, while no reference is made to the problem of inequality in community’s access to local natural resources. Confronted with such structural challenges, it is argued that “struggle for village autonomy” will hardly lead to significant social transformation without involving attempts to establish just and sustainable natural resource regime. At the same time, “the struggle for social-ecological justice” will never emerge as village’s collective agenda without attempts to deepen democracy within the village. Accordingly, this article offers “democratization of rural natural resource governance” as a strategic convergence between two previous struggles: “village autonomy” and “social-ecological justice”. It is pursued through three inter-related agenda: strengthening village’s authority concerning natural resource issues, democratizing socio-agrarian relations in the village, and addressing rural crises in order to revitalize productive forces in the village.